2021
DOI: 10.33774/chemrxiv-2021-5714s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catalytic Enantioselective Nucleophilic Desymmetrisation of Phosphonate Esters

Abstract: Compounds containing one or more stereogenic phosphorous atoms in the P(V) oxidation state are important to chemistry, biology and medicine. 1 These include marketed antiviral drugs such as Tenofovir alafenamide and Remdesivir, 2 an effective treatment for Ebola which has also recently been approved for use against SARS-CoV-2 in the US.Existing approaches for the stereoselective synthesis of P-stereogenic centers, while elegant, remain mostly diastereoselective, with catalytic enantioselective approaches remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…An alternative approach was demonstrated by Miller and co-workers in the catalytic, stereodivergent synthesis of P-stereogenic oligonucleotides from phosphoramidites via chiral phosphoric acid catalysis (24). Finally, in work that appeared as this study was being completed, Dixon and co-workers reported a catalytic, enantioselective desymmetrization of diaryl phosphonate esters by substitution with orthosubstituted phenols (25). While high levels of stereoselectivity were achieved in these catalytic, nucleophilic substitution reactions, each is limited to a narrow class of nucleophiles that are not further displaced.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach was demonstrated by Miller and co-workers in the catalytic, stereodivergent synthesis of P-stereogenic oligonucleotides from phosphoramidites via chiral phosphoric acid catalysis (24). Finally, in work that appeared as this study was being completed, Dixon and co-workers reported a catalytic, enantioselective desymmetrization of diaryl phosphonate esters by substitution with orthosubstituted phenols (25). While high levels of stereoselectivity were achieved in these catalytic, nucleophilic substitution reactions, each is limited to a narrow class of nucleophiles that are not further displaced.…”
Section: Introductionmentioning
confidence: 99%
“…stereoselective construction of P-stereogenic compounds(17,18). https://doi.org/10.26434/chemrxiv-2024-1ph89 ORCID: https://orcid.org/0000-0001-7952-3661 Content not peer-reviewed by ChemRxiv.…”
mentioning
confidence: 99%